LITERATURE STUDY OF THE BENEFITS OF ROSELLA PETALS (Hibiscus sabdariffa L.) AS ANTIHYPERTENSION - Kirwanto, Ag.; Indarto; Suhendriyo; EP, Sari (Poltekkes Kemenkes Surakarta, 2024)
Roselle (Hibiscus sabdariffa L.) has various benefits as antihypertensive, antifungal, anti-inflammatory, antidiabetic, antioxidant and antibacterial. This research aims to determine the benefits of roselle petals as an antihypertensive using a literature study method with data sources obtained from a data base. Searches for scientific articles were carried out on databases, namely Google Scholar, Semantic Scholar and Research Gate using the keywords